Implementasi Kodular dalam Perancangan Aplikasi Manajemen Inventaris Sekolah Berbasis Android - Yanti, Rahma; Annas, Firdaus; Yuspita, Yulifda Elin; Darmawati, Gusnita (Yayasan Lembaga Studi Makwa, 2023)
The aim of this research is to design an Android-based school inventory application to assist in managing item data, making it easier to borrow and return items. This is due to a problem that Islamic boarding schools do not yet have an inventory application for goods at the boarding school, currently the data collection carried out by the Islamic boarding school is still less effective. This can be seen from the inventory of many schools that do not yet have item codes, there have been cases where items were lost where the code for the item was not known. The data for recording goods should be real with the data collected at school. Complete this research using the Research and Development (R&D) model. This model is applied to create a particular product and test the product. The R&D model in this research applies the ADDIE development model with five stages, namely Analyze, Design, Develop, Implement, and Evaluate. Product testing is carried out using validity tests, practicality tests and effectiveness tests. The findings of this research produce coding of goods in the form of a QR Code, making it easier to manage cottage inventory data. The results of the product validity test with two experts in the field of programming and one expert in the field of linguistics obtained a value of 0.88, categorized as valid, the results of the practicality test with fifteen teachers at the Diniyyah Pasia Modern Islamic Boarding School obtained a value of 0.91, categorized as level The practicality is very high, and the results of the effectiveness test with one head teacher of the computer laboratory and one person from the administration section obtained a score of 0.88, categorized as a high level of effectiveness. So from these results it can be concluded that the Android-based School Inventory Management Application product using Kodular at the Diniyyah Pasia Modern Islamic Boarding School is valid, practical and effective to use. Abstrak Tujuan dari penelitian ini untuk merancang aplikasi inventaris sekolah berbasis android untuk membantu dalam pengelolaan data barang, kemudahan dalam peminjaman dan pengembalian barang. Hal ini disebabkan suatu permasalahan di pondok pesantren belum memiliki aplikasi inventaris barang di pondok tersebut, pada saat ini pendataan barang yang dilakukan oleh Pondok masih kurang efektif. Hal ini dapat dilihat dari inventaris sekolah banyak yang belum memiliki kode barang, pernah terjadinya kehilangan barang yang mana barang tersebut tidak diketahui kodenya. Semestinya data pencatatan barang harus real dengan pendataan barang disekolah. Menyelesaikan penelitian ini menggunakan model Research and Development (R&D). Model ini diterapkan untuk membuat sebuah produk tertentu dan menguji produk tersebut. Model R&D pada penelitian ini menerapkan model pengembangan ADDIE dengan lima tahapan yaitu Analyze, Design, Develop, Implement, dan Evaluate. Pengujian produk dilakukan dengan uji validitas, uji praktikalitas, dan uji efektivitas. Temuan penelitian ini yaitu menghasilkan pengkodean barang dalam bentuk QR Code sehingga memudahkan dalam pengelolaan data inventaris pondok. Hasil uji validitas produk dengan dua orang ahli di bidang pemrograman dan satu orang ahli di bidang kebahasaan diperoleh nilai 0,88 dikategorikan valid, hasil uji praktikalitas dengan limabelas orang bapak/ibuk guru di Pondok Pesantren Modern Diniyyah Pasia diperoleh nilai 0,91 dikategorikan dengan tingkat kepraktisan sangat tinggi, dan hasil uji efektivitas dengan satu orang guru kepala labor komputer dan satu orang bagian tata usaha diperoleh nilai 0,88 dikategorikan dengan tingkat keefektifan tinggi. Maka dari hasil tersebut dapat disimpulkan produk Aplikasi Manajemen Inventaris Sekolah Berbasis Android Menggunakan Kodular di Pondok Pesantren Modern Diniyyah Pasia sudah valid, praktis, dan efektif untuk digunakan.